Rapid, accurate, and novel diagnostic technique for respiratory pathogens: Clinical application of loop-mediated isothermal amplification assay in older patients with pneumonia, a multicenter prospective observational study - Wei, Shanchen; Wang, Lina; Shi, Mingwei; Li, Jun; Sun, Chunping; Liu, Yingying; Zhang, Zhi; Wu, Yiqun; Huang, Lei; Tang, Fei; Lv, Liping; Mu, Xiangdong; et al. (Frontiers in Microbiology, 2022)
Loop-mediated isothermal amplification (LAMP) is a novel nucleic acid amplification method using only one type of enzyme that can amplify DNA with high specificity, efficiency and rapidity under isothermal conditions. Chips for Complicated Infection Detection (CCID) is based on LAMP. To translate CCID into clinical application and evaluate its diagnostic value for pneumonia, 81 older patients with pneumonia were prospectively enrolled from January 1 to July 23, 2021, and 57 sputum/airway secretion and 35 bronchoalveolar lavage fluid samples were collected and analyzed by CCID and conventional microbiological tests (CMTs). Samples were collected, transported, monitored, and managed by a multidisciplinary team using a sample management information system. CCID turnaround time was 50 min, and the detection limit was 500 copies/reaction. The percentage of positive samples was significantly higher using CCID than CMTs, especially for Klebsiella pneumoniae (odds ratio [OR], 9·0; 95% confidence interval [CI], 1·1–70·5; P<0·05), Enterococcus faecalis (OR, ∞; P<0·01), Stenotrophomonas maltophilia (OR, ∞; P<0·01), fungi (OR, 26·0; 95% CI, 3.6–190.0; P<0·01), and viruses (CCID only; P<0·01). In addition, the percentage of positive results was significantly higher using CCID than CMTs in patients who used antibiotics for more than 3 days (91·9% vs 64·9%; P<0·01). Analyzing clinical impact, fifty-five cases (59·8%) benefited from CCID. These results demonstrate that CCID allows the rapid and accurate detection of pneumonia in older patients. Moreover, this technique is less affected by previous antibiotic treatment and can improve patient care.